Estimations of the Roman Life Expectancy Using Ulpian´s Table - Pflaumer, Peter (American Statistical Association, 2015)
In this paper a life table for the Roman population is constructed using Ulpian’s table. This table can be regarded as a tool to compute the value of an annuity taking into account the age of the beneficiary. The Gompertz distribution and some of its extensions are applied for the life table construction. It is shown that the Roman life table can be represented by a five-parameter formula, which consists of three terms. Since the life expectancy at birth depends on the unknown infant mortality, different assumptions are made. Simulations show that a range of the life expectancy between 20 and 30 years is quite possible. Finally, it is discussed whether Ulpian´s table represents annuities or life expectancies. It cannot be excluded that the values in Ulpian’s table represent annuities premiums based on an interest rate of about 1.5%.
Keywords: Life Table; Gauss Mortality Law; Lazarus Distribution; Roman Demography; Gompertz-Makeham; Mortality Law; 310